Thyroid cancer in women of reproductive age: Key issues for the clinical team - María Fernanda Toro-Wills; Angélica Imitola-Madero; Angelina Alvarez-Londoño; Abraham Hernández-Blanquisett; María Cristina Martínez-Ávila (Women's Health, 2022)
Women who are fertile experience a significant burden from thyroid cancer. In reality, delaying childbirth is the current trend in maternity. Women who have thyroid cancer may later want to get pregnant after it has been treated, which presents a multidisciplinary issue for their doctors. A variety of specialists are frequently involved in the treatment of thyroid cancer. This review aims to address the key elements of the strategy and places special emphasis on the significance of fertility in women with thyroid cancer diagnosis and remission. We will cover topics including the role of thyroid hormones in pregnancy and fertility.